Islamic Feminism as a Rising Field of Inquiry in Contemporary Times - Bahar , Ruqayya (South Asian Journal of Social Sciences and Humanities, 2021)
Over the past few years an emerging class of writers, particularly women, have taken up the task of analysing Islam and the Quran from their perspective. In the process of rereading and reinterpretation of the Holy text, women bring about their own personal experiences and doubts into consideration for a better understanding. These women writers aim to highlight how the previous interpretations were moulded to satisfy male interests only. They deny any such beliefs and interpretations which only serve the male members of the community, neglecting their women counterparts. Reading it through the lens of Islamic feminists, therefore, subverts all such beliefs.